PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL AUDITOR TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - CHRISTINA GUNAEKA NOTOPRASETIO (Universitas Katolik Widya Mandala Surabaya, 2012)
This research was aimed to investigate the influence of emotional intelligence and spiritual auditor on the performance of auditors in public accounting office in Surabaya. The analysis was based on respondents' answers obtained through a questionnaire distributed in Surabaya. The population of this research is a public accountant who was in Surabaya. This study uses a Multiple Linear Regression, F test used to determine the effect of intelligence and spiritual emosional auditor, and the t test used to determine the effect of emotional intelligence and spiritual auditor separately to the performance of auditors. The analysis showed that emotional and spiritual intelligence auditor significant effect on the performance of auditors.